2000
DOI: 10.1627/jpi1958.43.114
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-deep Hydrodesulfurization of Kerosene for Fuel Cell System. (Part 2). Regeneration of Sulfur-poisoned Nickel Catalyst in Hydrogen and Finding of Auto-regenerative Nickel Catalyst.

Abstract: An idea to regenerate sulfur-poisoned Ni catalyst in flowing H2 was tried. That is, sulfur-poisoned Ni catalyst particles are mixed with ZnO fine particles in a H2 atmosphere at 600K, then the each poisoned catalyst particle would releases a few ppb of H2S through the H2 atmosphere and the released H2S would be accepted on neighboring ZnO particles.Then, a million-fold effective improvement in the regeneration of sulfur-poisoned Ni catalyst in a flow of H2 would be realized.After only a 90h of trial operation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 1 publication
1
46
0
Order By: Relevance
“…A similar mechanism was recently proposed by Aksenov et al [26] and Chica et al [27,28]. Tawara and co-workers [29] reported that 12.3% Ni/ ZnO was applied as a model catalyst for adsorptive ultradeep HDS (UD-HDS) of kerosene in a stream of H 2 containing 25% CO 2 at 600 K. The experiments results showed that residual sulfur in the treated kerosene was not detectable ( < 0.06 wt-ppm) even after 800 h of operation. They first reported that the regeneration of the sulfur poisoned Ni catalyst in a H 2 stream was realized and the automatic regenerative Ni catalyst for adsorptive HDS was demonstrated.…”
Section: Researches On Mechanismsupporting
confidence: 77%
“…A similar mechanism was recently proposed by Aksenov et al [26] and Chica et al [27,28]. Tawara and co-workers [29] reported that 12.3% Ni/ ZnO was applied as a model catalyst for adsorptive ultradeep HDS (UD-HDS) of kerosene in a stream of H 2 containing 25% CO 2 at 600 K. The experiments results showed that residual sulfur in the treated kerosene was not detectable ( < 0.06 wt-ppm) even after 800 h of operation. They first reported that the regeneration of the sulfur poisoned Ni catalyst in a H 2 stream was realized and the automatic regenerative Ni catalyst for adsorptive HDS was demonstrated.…”
Section: Researches On Mechanismsupporting
confidence: 77%
“…The measurement7) was carried out by TPD-MS using a flow-through cell and the GC-NO-pulse procedure as Eqs. (1) and (2). The complicated analysis of the measured data was carried out using software developed in this laboratory7).…”
Section: Introductionmentioning
confidence: 99%
“…As represented in XRD characterization, there is no obvious reflection for crystalline ZnO and Al 2 O 3 in the sample NiZnO/ Al 2 O 3 , while broad diffraction peaks of ZnAl 2 O 4 are found, it indicates that there are strong interactions between ZnO and Al 2 O 3 . Tawara et al 10 reported that Ni/ZnO is an autoregenerative adsorptive UD-HDS catalyst, the ZnO support is regarded to regenerate sulfur-poisoned surface Ni to active surface Ni by accepting H 2 S. In the reactive adsorption desulfurization system, ZnO is considered to the active component, while ZnAl 2 O 4 belongs to the non-active component. So the formation of ZnAl 2 O 4 in the sample NiZnO/ Al 2 O 3 may be the reason for lower activity.…”
Section: Resultsmentioning
confidence: 99%